Molecular visualization / Foong Yee Peng - Foong , Yee Peng (2005)
There are many programs for molecular visualization such as RasMol, Quanta, GRASP, SETOR. Amira, etc. They all perform many of the same basic tasks; they read in molecular structure data, perform some analysis, and display the results Visualization programs usually analyze the data to display some aspects of it, while programs for analysis often return their results as detailed textual information. As visualization and analysis tasks become more complex and the expectations for programs continues to rise, it has become crucial to build a powerful molecular visualization system that can speed up the researches in chemical, pharmaceutical and medical areas. Thus, the purpose of this project is to discover a system that enables segmenting, rendering and visualization of static and dynamic molecular data at an appropriate speed.